Analisis Tingkat Kecelakaan dan Penanganannya pada Jalan Tjilik Riwut di Desa Pelantaran - hariyanto, Fivi Asriyanti Hariyanto; Salonten; Murniati (Journal Serambi Engineering, 2023)
The traffic flow on the Pelantaran Village route has consistently increased over the years. To ensure road safety, a thorough investigation is necessary to determine the frequency and severity of accidents on Pelantaran Village Road, from kilometre 67 to kilometre 77. The initial step involves collecting data through direct visual observations on Tjilik Riwut Road in Pelantaran Village, which will serve as primary data. In addition, secondary data is obtained from the Kotawaringin Timur Resort Police (Polres) and the Kalimantan Tengah National Road Implementation Centre. To identify accident-prone points, also known as blackspots, historical accident data from the past two to three years is analyzed. The research employed the Equivalent Accident Number (EAN) methodology, the Batas Kontrol Atas (BKA) technique, and the Upper Control Limit (UCL) approach. The findings indicate that the accident rate was 65.68 in 2020, decreased to 10.39 in 2021, and increased to 17.30 in 2022. The mean accident rate for 2020 and 2022 was 31.12. Police statistics identify human error as the primary cause of accidents. After analysing the road conditions, including the presence of side obstructions, parked cars, the absence of traffic signs, and inadequate road illumination during nighttime hours, it can be concluded that the road is unsafe for driving.